2018
DOI: 10.1186/s12879-018-3056-2
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of M. leprae DNA detection in asymptomatic household contacts

Abstract: BackgroundCharacterization of the Mycobacterium leprae genome has made possible the development of Polymerase Chain Reaction (PCR) systems that can amplify different genomic regions. Increased reliability and technical efficiency of quantitative PCR (qPCR) makes it a promising tool for early diagnosis of leprosy. Index cases that are multibacillary spread the bacillus silently, even before they are clinically diagnosed. Early detection and treatment could prevent transmission in endemic areas.MethodsIn this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 22 publications
5
28
0
1
Order By: Relevance
“…Previous reports from our group have also demonstrated the presence of M. leprae DNA in scrapes and blood samples as well as high levels of antibodies to M. leprae recombinant proteins in household contacts [26,27]. These ndings strongly suggest the subclinical infection in household contact.…”
Section: Discussionsupporting
confidence: 73%
“…Previous reports from our group have also demonstrated the presence of M. leprae DNA in scrapes and blood samples as well as high levels of antibodies to M. leprae recombinant proteins in household contacts [26,27]. These ndings strongly suggest the subclinical infection in household contact.…”
Section: Discussionsupporting
confidence: 73%
“…Previous reports from our group have also demonstrated the presence of M. leprae DNA in scrapes and blood samples as well as high levels of antibodies to M. leprae recombinant proteins in household contacts [26,27]. These ndings suggest that household contact should be monitored for putative subclinical infection.…”
Section: Discussionsupporting
confidence: 69%
“…Hastings RC group has described increasing family clustering as the endemicity level reduces since 1994 [ 30 ], which means in the low endemic area of Shandong province, surveillance of the RFT patients and their contact individuals is much more important. Numerous studies show that individuals living with a patient with untreated leprosy have a higher risk of developing clinical disease [ 6 , 31 ]. A 25-year follow-up research study in Sulawesi, Indonesia showed that 28 of 101 (28%) newly diagnosed patients were identified as household contacts and 36 (36%) identified as neighbors [ 8 ].…”
Section: Discussionmentioning
confidence: 99%